Development and validation of year five geometrical measurement skills instrument - Siti Nur Annisa Mohd Nasser; Lim Hooi Lian (International Journal of Evaluation and Research in Education (IJERE), 2021)
Geometrical measurement is one of the most difficult fields in primary school mathematics and regularly found to be an area of weaknesses. The factors affecting the low understanding is due to the lack of valid and reliable assessment instruments. Thus, this study aimed to develop and validate a Geometrical Measurement Skill Instrument (GMSI) to assess Year Five National school pupils’ geometrical measurement skills in geometrical measurement. GMSI was developed by applying the Structure of Observed Learning Outcomes (SOLO) Taxonomy and was constructed in the super item format which consisted of 24 items altogether. This study applied a survey approach to assess 132 Year Five pupils’ geometrical measurement skills. The content validity was examined using the content validity index (CVI) analysis. For the construct validity, data were obtained and analyzed using the Rasch analysis. From the CVI analysis, the results showed that GMSI could be used for the pilot study. Results for the construct validity indicated that GMSI fulfilled the psychometric properties and is valid and reliable. Hence, the results could help teachers and pupils to diagnose the strength and weaknesses of geometrical measurement and help them to plan systematic remedy to improve teaching and learning.